Hostages of Me - Biering, Tue (Peripeti, 2023)
Hostages of Me by Tue Biering and Hvad har vi egentlig haft gang i? Etiske, sociale og kunstneriske undersøgelser by Jeppe Kristensen: In two articles, the founders of FIX&FOXY are reflecting on how the production company can develop theater and performances, in order to make the audience reflect on societal dilemmas.